Posterior Urethral Valves: Experience of a Level III Hospital - Almeida, Sónia (2019)
Introduction: The posterior urethral valves (PUV) are an important cause of congenital urinary tract obstruction affecting male children. Our aim in this study was to characterize the evolution of a children group with PUV with identification of possible risk factors to chronic kidney disease (CKD). Methods: Retrospective analysis of PUV children diagnosed between January 1999 and January 2017 in a level III hospital. Data collected included: clinical, analytical and imagiological findings, treatment and evolution. Statistical tests were realized using: Excel 2016® e Epi Info 7®, with p < 0.05 considered significant. Results: During the studied period, we identified 23 cases of VUP. The diagnosis was prenatal in 16 and four of seven were diagnosed before age one. The clinical presentation was: acute renal failure (n= 11), isolated urinary tract infections (UTI) (n= 4) and poor urinary stream (n= 3). Median creatinine was 151 μmol/L. All 23 children presented renal and upper urinary tract dilatation, (bilateral in 22), 21 had parenchymal changes and 19 had thickened wall bladder. Cistouretrography confirmed the diagnosis and revealed vesicoureteral reflux (VUR) in 15 cases, bilateral in 10. The main treatment was valve ablation by endoscopic fulguration, performed in all cases, one of them with a previous vesicostomy. The mean follow-up was 7.5 years. During that time, 14 presented recurrent UTI’s, seven remained with VUR and 11 with bladder dysfunction. Some needed other surgical procedures, like VUR correction (n= 3) and unilateral nephrectomy (n= 2). Five cases (21.5%) presented CKD stage ≥ 3, with four cases needing dialysis around 9.3 years of mean age. The recurrent UTI’s and bilateral VUR were associated with evolution to that stage (p 0.03 and p 0.049 respectively). Conclusion: PUV remains a frequent aetiology of CKD, despite timely and accurate diagnosis and treatment.